The Influence of Gen Z Characteristics and Company Strategy on Turnover Intention - Yoga Anggara; Novrihan Leily Nasution; Meisa Fitri Nasution (International Journal of Science, Technology & Management, 2026)
This study aims to analyze the influence of Generation Z characteristics and company adaptation strategies on the turnover intention of Generation Z employees at the startup company APINDIGITAL.ID. Using an explanatory quantitative approach with a saturated sample of 25 respondents, the data were analyzed through multiple linear regression with SPSS. The t-test results show that Generation Z characteristics have a positive and significant effect on turnover intention (Sig. = 0.018 < 0.05), while company adaptation strategies do not have a significant effect partially (Sig. = 0.075 > 0.05). However, simultaneously both have a significant effect (F test, Sig. = 0.013 < 0.05) with a coefficient of determination (R²) of 32.6%. Generation Z characteristics are the dominant factor. This finding emphasizes the importance of understanding Generation Z characteristics for startups in designing adaptive retention strategies to reduce turnover intention.